2022
DOI: 10.1177/10398562211062465
|View full text |Cite
|
Sign up to set email alerts
|

The evidence for introducing case-finding for delirium and dementia in older medical inpatients in a New Zealand hospital

Abstract: Objective The aim of this project was to make the case to the managers of a large urban teaching hospital in New Zealand for the introduction of systematic case-finding for pre-existing cognitive impairment/dementia in older hospital inpatients that screen positive for delirium. Method Two hundred consecutive acute admissions aged 75+ in four medical wards were assessed using the 4AT assessment tool for delirium and the Alzheimer Questionnaire (AQ) for pre-existing cognitive impairment/dementia. Length of stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…All outcomes were worse for people with delirium (with or without dementia) compared to people with dementia only. The first two findings for length of stay and mortality replicated the findings in our previous analysis of a smaller sample in NZ, 16 in which people who screened positive for delirium (with or without dementia) had double the length of stay and a two-fold risk of death at one year. Likewise, our findings replicated those of recent international studies, which also reported that, compared to patients with no cognitive impairment, patients with delirium and delirium superimposed on de-mentia doubled the length of stay and increased the risk of mortality by two to three times.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…All outcomes were worse for people with delirium (with or without dementia) compared to people with dementia only. The first two findings for length of stay and mortality replicated the findings in our previous analysis of a smaller sample in NZ, 16 in which people who screened positive for delirium (with or without dementia) had double the length of stay and a two-fold risk of death at one year. Likewise, our findings replicated those of recent international studies, which also reported that, compared to patients with no cognitive impairment, patients with delirium and delirium superimposed on de-mentia doubled the length of stay and increased the risk of mortality by two to three times.…”
Section: Discussionsupporting
confidence: 79%
“…Due to the use of routinely collected data, we were also able to include everyone who had a delirium screen, whereas participants who are too unwell to consent to participate may be excluded in prospective studies. Along with other previous studies, 10,14 have shown that we can use routinely collected data to replicate the findings from similar prospective cohort designs, 5,9,[11][12][13]16 which, although not as methodologically rigorous, demonstrates the utility and cost-effectiveness of this study method.…”
Section: Strengths and Limitationsmentioning
confidence: 62%
See 1 more Smart Citation
“…Our study highlights crucial clinical and public health insights, revealing that IGT individuals developing T2D face a heightened 10‐year dementia incidence rate. It underscores the need for healthcare providers to screen for dementia proactively and offer targeted counselling early on, especially within a decade of diabetes diagnosis 40 …”
Section: Discussionmentioning
confidence: 99%
“…It underscores the need for healthcare providers to screen for dementia proactively and offer targeted counselling early on, especially within a decade of diabetes diagnosis. 40 Preventing T2D onset in IGT individuals could reduce dementia incidence, 29 emphasizing public health's need for targeted dementia screening, especially for high-risk groups. Prioritizing deprived or minority groups, revealed to have higher dementia rates, underscores the importance of lifestyle interventions, such as smoking cessation and physical activity, in dementia prevention.…”
Section: F I G U R Ementioning
confidence: 99%